Model Pembelajaran Inkuiri Terbimbing dan Peningkatan Hasil Belajar Siswa Pada Pola Bilangan - Tamam, Muhammad Badru (FKIP Universitas Islam Jember, 2021)
Classroom action research on the application of the Guided Inquiry learning model to improve student learning outcomes in the material pattern VIII MTs. Miftahul Ulum academic with 14 students as respondents. The method used in this research is the method of observation, documentation, interviews, and tests. Data analysis using qualitative analysis and quantitative analysis. The research was conducted in 2 cycles with 2 meetings in each cycle. In the first cycle, the activities and student learning outcomes are said to be successful with the criteria of at least 65% of all students, while in the second cycle, the activities and student learning outcomes are said to be successful with the criteria of 75% of all students. Based on the results of research on student learning outcomes the first cycle obtained a percentage of 42.8% and the second cycle with a percentage of 92.8%.